Parametric crystal optics of nonmagnetic ferroics - Vlokh, O.G. (Condensed Matter Physics, 1998)
Proceeding from the symmetry principles of crystal physics and thermodynamics we analyze parametrical optical phenomena induced by external fields of different kind and structural phase transitions in ferroelectrics and ferroelastics. Special attention is paid to the phenomena of spatial dispersion (electro- and piezogyration). A phenomenological approach to the description of these phenomena is illustrated by the most expressive experimental results obtained for the following crystals: KH₂₍₁₋x₎ D₂x PO₄ (KDP, DKDP), K₂H₂AsO₄ (CDA), RbH₂PO₄ (RDP), Pb₅(Ge₍₁₋x₎ Six)₃ O₁₁, Pb₃ (PO₄ )₂ , K₂ Cd₂ (SO₄ )₃ , (NH₃ CH₂ COOH)₃H₂ SO₄ (TGS), and NaKC₄H₄O₆ 4H₂O (RS). Apart from new effects in the crystals of the A₂BX₄ group with incommensurately modulated structure, in particular, crystals [N(CH₃)₄]₂ ZnCl₄ , [N(CH₃)₄ ]₂ FeCl₄ , K₂ ZnCl₄ , K₂ ZnCl₄ , Co²⁺ are considered.